CircularEconomy4Colombia: Bootcamp Highlight - CGIAR Accelerate for Impact Platform (2025)
The CircularEconomy4Colombia Innovation Challenge is an initiative aimed supporting Colombia’s transition to a circular economy within the agri-food sector. The challenge seeks to boost and scale up high-impact, science-backed, context-specific solutions that enhance resource efficiency, reduce waste and deforestation, and promote sustainable development in Colombia. As part of this challenge, 21 selected teams had the opportunity to join a fully funded 3-day in-person bootcamp on 9-11 October, 2024, at the Alliance Bioversity and CIAT Palmira Campus in Colombia.